Alteration of mixture toxicity in nonferrous metal mine tailings treated by biochar. (1st July 2020) - Gu, Jihai; Yao, Jun; Duran, Robert; Sunahara, Geoffrey; Zhou, Xiaoqi
Abstract: Nonferrous metal mining activities produce enormous amounts of tailings that contain high concentrations of toxic chemicals threatening human health and the environment. This risk could be alleviated using remediation agents such as biochar, as proposed by others. However, contradictory evidence indicates that biochar can increase or sometimes decrease bioavailable concentrations depending on the selection of metal(loid)s in mine tailings. Here three biochars derived from different raw stocks were used to treat mine tailings samples. Chemical analyses indicated that all biochars favored the stabilization of Cd, Cr, Cu, Pb, and Zn, as well as the mobilization of As and Sb. The barley root elongation bioassay showed that the tailings toxicity was only partially diminished (up to 55.8%) or even elevated (up to 20.7%) by biochar treatment. Similar results were also observed from microbial enzyme assays (increased up to 28.3% or decreased up to 24.0%). Further analyses showed that these toxic effects correlated well with the relative toxicity index ( R 2  = 0.66 to 0.88). Toxicity testing coupled with the use of a toxicity prediction model presented here suggested that the release of As and Sb from tailings compromised the favorable effects of biochar treatment on toxic cationic metals. Such information is of paramount importance when taking countermeasures for improving bioremediation technologies. Graphical abstract: Image 1 Highlights: Biochar decreased mobility of metals and increased that of metalloids in tailings. Phytotoxicity was diminished < 55.8% or increased < 20.7% using different biochars. Microbial activities increased < 28.3% or decreased < 24.0% using different biochars. Release of metalloids compromised biochar treatment on mine tailings. Relative toxicity index can predict tailings mixture toxicity.